Religiocentrism and Voting Intention Among University Students in the 2024 Indonesian General Election: A Social Identity Perspective - Tery Setiawan; Trisa Genia C. Zega; Nurul Arbiyah (Universitas Mercu Buana Yogyakarta, 2025)
This study aimed to examine the extent to which religious identity and past experience of political participation can explain individuals' intention to vote in the 2024 general election in Indonesia. A total of 320 respondents were recruited through convenience sampling techniques in Bandung and Cimahi. The results show that only the religiocentrism dimension was positively associated with the intention to vote, while other dimensions such as religious practice and intratextual fundamentalism were negatively related. In addition, the results showed that the experience of political participation in the past was not positively related to the intention to vote in the 2024 general election. This could be explained through religiocentrism’s tendency to encourage individuals to view their religious ingroup as better than religious outgroups, leading them to choose leaders who align with the values of their religious identity. On the other hand, past experience of political participation might have caused individual disappointment with political practices in Indonesia which are still tainted by corruption and nepotism, so they felt that their political participation had no significant impact. These findings provided a new perspective on individual’s intention to use their political rights in Indonesian general election.